Residential Irrigation Water Costs in Osceola County and Orange County, Florida - Nick Taylor; Tricia Kyzar; Pierce Jones; Kaitlin O. Robb Price (EDIS, 2020)
Interest in understanding water use and irrigation costs has risen in recent years. This case study is a 5-page evaluation of water use and associated costs for residential landscape irrigation in Osceola County and Orange County, Florida. Homeowners in central Florida can use the results to assess their water consumption and bills in relation to similar homes in the area. Written by Nick Taylor, Tricia Kyzar, Pierce Jones, and Kaitlin O. Robb Price, and published by the UF/IFAS Department of Agricultural and Biological Engineering, December 2019. https://edis.ifas.ufl.edu/ae536